Influence of muscle tension type on bioelectrical activity and regional blood flow in lower limbs of skilled boxers - Neupokoev, S. N.; Bredikhina, J. P.; Guseva, N. L. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to assess the influence of various types of muscle tension on bioelectrical activity and regional blood flow in the lower limbs of skilled boxers. The conclusions of the study were: The use of sport outfit that limits the traumatic impact on the hands (boxing gloves) during the training process enables skilled athletes to perform movements in line with the optimal motor-coordination parameters, without any detectable effects of distractive factors. Performance of punches of the explosive ballistic muscle tension type contributes to more significant involvement of the lower limb muscles and improves blood filling and venous outflow in these muscles. At the same time, performance of punches using the standard sport outfit prevents from preserving the best biomechanical characteristics of movement, which adversely affect the athletic training process of boxers.